Informal employment in emerging and transition economies - Fabián Slonimczyk (IZA World of Labor, 2022)
In developing and transition economies as much as half the labor force works in the informal sector (or "shadow economy"). Informal firms congest infrastructure and other public services but do not contribute the taxes needed to finance them. Informal workers are unprotected against such negative shocks as ill-health, but for certain groups there can be scarce opportunities to enter the formal sector meaning informal employment is the only feasible option. Reducing informality requires better enforcement, more reasonable regulation, and economic growth.
Keywords: J46; 330; informality; shadow economy; mobility; exclusion